Listing of Food Service Equipment - National Sanitation Foundation, Ann Arbor, MI. Testing Lab.; National Sanitation Foundation, Ann Arbor, MI. Testing Lab. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
A comprehensive listing of food service equipment including--(1) companies authorized to use the National Sanitation Foundation seal of approval, and (2) equipment listed as meeting NSF standards including soda fountains, spray-type dishwashers, dishwashing equipment, cooking equipment, commerical cooking and warming equipment, freezers, refrigerators, food preparation equipment, ice-making equipment, food vending machines, special equipment, cloth towel dispensers. A final section presents an index to company seal of approval numbers. (RH)
Availability: National Sanitation Foundation, Testing Laboratory, 2355 West Stadium Boulevard, P. O. Box 1468, Ann Arbor, Michigan 48106 ($1.00).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Public Health; Equipment Standards; Equipment; Food Service; Food Standards; Sanitation